Electrical characterization of chemical and dielectric passivation of InAs nanowires. (13th October 2016) - Holloway, Gregory W; Haapamaki, Chris M; Kuyanov, Paul; LaPierre, Ray R; Baugh, Jonathan
Abstract: The native oxide at the surface of III−V nanowires, such as InAs, can be a major source of charge noise and scattering in nanowire-based electronics, particularly for quantum devices operated at low temperatures. Surface passivation provides a means to remove the native oxide and prevent its regrowth. Here, we study the effects of surface passivation and conformal dielectric deposition by measuring electrical conductance through nanowire field effect transistors treated with a variety of surface preparations. By extracting field effect mobility, subthreshold swing, threshold shift with temperature, and the gate hysteresis for each device, we infer the relative effects of the different treatments on the factors influencing transport. It is found that a combination of chemical passivation followed by deposition of an aluminum oxide dielectric shell yields the best results compared to the other treatments, and comparable to untreated nanowires. Finally, it is shown that an entrenched, top-gated device using an optimally treated nanowire can successfully form a stable double quantum dot at low temperatures. The device has excellent electrostatic tunability owing to the conformal dielectric layer and the combination of local top gates and a global back gate.